2019
DOI: 10.3390/su11216157
|View full text |Cite
|
Sign up to set email alerts
|

Older People, Mobility and Transport in Low- and Middle-Income Countries: A Review of the Research

Abstract: Older populations are rising globally, which in high-income countries has helped to generate a growing literature on the impact of ageing on travel requirements and transport policy. This article aims to provide an initial assessment of the state of knowledge on the impact on transportation policy and usage of the increasing numbers of older people in low- and middle-income countries (LAMICs), through a review of the literature relating to older people and transportation. As both the academic and policy/practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Furthermore, health risks attributable to air pollution and extreme weather could be exacerbated through active transport in adults living in the most deprived areas. Indeed, walking or biking might be the only travel mode in adults with low income [106]. Previous reviews also suggested a possible "positive impact" of temperature increases during cold seasons [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, health risks attributable to air pollution and extreme weather could be exacerbated through active transport in adults living in the most deprived areas. Indeed, walking or biking might be the only travel mode in adults with low income [106]. Previous reviews also suggested a possible "positive impact" of temperature increases during cold seasons [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Not all drugs needed for managing chronic conditions among older adults are covered by the NHIS and these are expensive in the open private market. 54 Also, the skill of the health provider was called into question. This observation is in tandem with Kelly et al, who reported that in general, healthcare workers lack adequate training and experience on how to deal with geriatric issues and the management of chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…It is also probable that the various facets of mobility affected by the aging process could be considered [ 22 ]. In a recent review, Gorman, Jones [ 23 ] suggested that social exclusion among older adults has many features that can be defined by their travel experience and have been discussed in the studies that focus on accessibility and transport needs obliquely. Thus, social exclusion features are more substantial than deprivation of income alone and entail the absence of sociocultural and political participation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the narrow biomedical model and physical environmental characteristics, the mobility of older adults is very much dependent on a set of psychosocial factors including the social relationship within the household, their relatives and acquaintances; cultural norms and expectations; attitudes; life-course trajectories; and experiences of individuals and societies [ 23 , 25 ]. The impact of psychosocial influences on the mobility and use of public transportation is a crucial concern for older adults in reducing social exclusions [ 23 ]. Similarly, the World Health Organization acknowledged that mobility is affected by the instinctive potential and the surroundings in which older adults reside.…”
Section: Introductionmentioning
confidence: 99%